The East Flanders Prospective Twin Survey (EFPTS) - Cathérine Derom; Robert Vlietinck; Evert Thiery; Fernand Leroy; Jean‐Pierre Fryns; R. Derom (2002)
The East Flanders Prospective Twin Survey (EFPTS) is a registry of multiple births in the province of East-Flanders, Belgium. It has several unique features: it is population-based and prospective, with the possibility of long-term follow-up; the twins (and higher order multiple births) are ascertained at birth; basic perinatal data are recorded; chorion type and zygosity are established; and since 1969 placental biopsies have been taken and frozen at −20°C for later determination of genetic markers. The EFPTS is the only large register that includes placental data and allows differentiation of three subtypes of monozygotic (MZ) twins based on the time of the initial zygotic division: the dichorionic-diamnionic pairs (early, before the fourth day after fertilisation), the monochorionic-diamnionic pairs (intermediate, between the fourth and the seventh day post fertilisation), and the monochorionic-monoamnionic pairs (late, after the eight day post fertilisation). This added a new dimension to didymology (the science of twins; διδυμоσ= twins): the timing of twinning. Studies can be initiated on primary biases, those originating “in utero”. Such studies may throw new light on the controversy over the validity of the classic twin method, the consequences of early embryological events (before and just after implantation of the embryo), the origin of congenital malformations, the sex proportion of multiples, the gene-environment interactions as far as intrauterine environment is concerned, to name but a few.